Songs of the Serbian people : from the collections of Vuk Karadžić - Karadžić, Vuk Stefanović, 1787-1864; Holton, Milne; Mihailovich, Vasa D. (Series in Russian and East European studies., 1997)
In the early nineteenth century, Vuk Karadzic, a Serb scholar and linguist, collected and eventually published transcriptions of the traditional oral poetry of the South Slavs. It was a monumental and unprecedented undertaking. Karadzic gathered and heard performances of the rich songs of Balkan peasants, outlaws, and professional singers and their rebel heroes. His four volumes constitute the classic anthology of Balkan oral poetry, treasured for nearly two centuries by readers of all literatures, and influential to such literary giants as Goethe, Merimee, Pushkin, Mickiewicz, and Sir Wal.